Overcoming a fundamental time-domain performance limitation by nonlinear control - Hunnekens, B.G.B.; Wouw, N.v.d.; Nešić, D. (Automatica (Oxford), 2016)
It is well-known that fundamental performance limitations exist when using linear feedback control for linear systems. In this note, we present an example of a nonlinear control strategy that can achieve a time-domain performance specification that cannot be obtained by any linear controller. In particular, we present a variable-gain control approach that meets an overshoot requirement that cannot be met by any linear controller.